2022
DOI: 10.1007/s00701-021-05092-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of non-vestibular schwannomas in adult patients: a systematic review and consensus statement on behalf of the EANS skull base section Part II: Trigeminal and facial nerve schwannomas (CN V, VII)

Abstract: Background Non-vestibular schwannomas are relatively rare, with trigeminal and jugular foramen schwannomas being the most common. This is a heterogenous group which requires detailed investigation and careful consideration to management strategy. The optimal management for these tumours remains unclear and there are several controversies. The aim of this paper is to provide insight into the main principles defining management and surgical strategy, in order to formulate a series of recommendations. Methods A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 112 publications
0
12
0
Order By: Relevance
“…The main therapeutic goals consist in providing clinical improvement and local tumor control, while minimizing complication risks and quality-of-life impairment [ 59 , 60 , 61 ]. Microsurgical tumor resection represents the current mainstay treatment, by allowing decompression of the CVJ neuro-vascular structures and prompt symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main therapeutic goals consist in providing clinical improvement and local tumor control, while minimizing complication risks and quality-of-life impairment [ 59 , 60 , 61 ]. Microsurgical tumor resection represents the current mainstay treatment, by allowing decompression of the CVJ neuro-vascular structures and prompt symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, micro-Doppler assistance may minimize the risk of vascular injuries in case of tumors encasing arterial and venous structures of the posterior circulation [ 10 ]. Although modern surgical management is shifting towards less aggressive procedures and PTR [ 59 ], most of our pooled cases received GTR, suggesting that accurate treatment planning and approach selection optimize safe tumor exposure and neuro-vascular control, with achievable maximal resection. No standardized guidelines on extent of surgical resection currently exist, but several authors suggested to pre-operatively plan PTR or GTR on a case-by-case basis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations